Characterization of SARS-CoV-2 Omicron BA.4 and BA.5 isolates in rodents - Uraki, Ryuta; Halfmann, Peter J.; Iida, Shun; Yamayoshi, Seiya; Furusawa, Yuri; Kiso, Maki; Ito, Mutsumi; Iwatsuki-Horimoto, Kiyoko; Mine, Sohtaro; Kuroda, Makoto; Maemura, Tadashi; Sakai-Tagawa, Yuko; et al. (Nature (London), 2022)
The BA.2 sublineage of the SARS-CoV-2 Omicron variant has become dominant in most countries around the world; however, the prevalence of BA.4 and BA.5 is increasing rapidly in several regions. BA.2 is less pathogenic in animal models than previously circulating variants of concern 1 – 4 . Compared with BA.2, however, BA.4 and BA.5 possess additional substitutions in the spike protein, which play a key role in viral entry, raising concerns that the replication capacity and pathogenicity of BA.4 and BA.5 are higher than those of BA.2. Here we have evaluated the replicative ability and pathogenicity of BA.4 and BA.5 isolates in wild-type Syrian hamsters, human ACE2 (hACE2) transgenic hamsters and hACE2 transgenic mice. We have observed no obvious differences among BA.2, BA.4 and BA.5 isolates in growth ability or pathogenicity in rodent models, and less pathogenicity compared to a previously circulating Delta (B.1.617.2 lineage) isolate. In addition, in vivo competition experiments revealed that BA.5 outcompeted BA.2 in hamsters, whereas BA.4 and BA.2 exhibited similar fitness. These findings suggest that BA.4 and BA.5 clinical isolates have similar pathogenicity to BA.2 in rodents and that BA.5 possesses viral fitness superior to that of BA.2. Results indicate that the sublineages BA.4 and BA.5 of SARS-CoV-2 Omicron variants have similar pathogenicity to that of the BA.2 sublineage in rodents, highlighting the importance of evaluating viral replication and pathogenesis using clinical isolates.